2010
DOI: 10.1371/journal.pone.0009998
|View full text |Cite
|
Sign up to set email alerts
|

Co-Swarming and Local Collapse: Quorum Sensing Conveys Resilience to Bacterial Communities by Localizing Cheater Mutants in Pseudomonas aeruginosa

Abstract: BackgroundMembers of swarming bacterial consortia compete for nutrients but also use a co-operation mechanism called quorum sensing (QS) that relies on chemical signals as well as other secreted products (“public goods”) necessary for swarming. Deleting various genes of this machinery leads to cheater mutants impaired in various aspects of swarming cooperation.Methodology/Principal FindingsPairwise consortia made of Pseudomonas aeruginosa, its QS mutants as well as B. cepacia cells show that a interspecies con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 25 publications
4
51
1
2
Order By: Relevance
“…These data suggest that OmpA is most important during initial stages of Sodalis gut colonization, as cells that lack this protein can reach normal densities over time. Interestingly, previous studies using other model systems have shown that mutant bacteria can "cheat" their colonization defect by cross-feeding off relevant protein products produced by endogenous bacteria also present in the system (30,38,45,46). We thus investigated whether Sodalis ⌬OmpA cells are able to colonize wild-type tsetse by cheating off the Sodalis naturally found in these flies.…”
Section: Gmmmentioning
confidence: 99%
“…These data suggest that OmpA is most important during initial stages of Sodalis gut colonization, as cells that lack this protein can reach normal densities over time. Interestingly, previous studies using other model systems have shown that mutant bacteria can "cheat" their colonization defect by cross-feeding off relevant protein products produced by endogenous bacteria also present in the system (30,38,45,46). We thus investigated whether Sodalis ⌬OmpA cells are able to colonize wild-type tsetse by cheating off the Sodalis naturally found in these flies.…”
Section: Gmmmentioning
confidence: 99%
“…I reasoned that due to its immunity to cheating and its global benefit to the population, the diverged QS strain (R 2 S 2 ) would perform better than the original QS strain (R 1 S 1 ) when each strain competes with the intermediate strain R 2 S 1 in a structured population (18)(19)(20). I analyzed the two competitions in the bottlenecked growth model for various bottleneck sizes ( Fig.…”
Section: Divergence Is Positively Selected By Rounds Of Cheating Andmentioning
confidence: 99%
“…From a social perspective these can be characterized as "public goods"-costly actions to the individual that benefit the whole population (SI Text, section 1). As such, QS was shown both theoretically (14-16) and experimentally (17)(18)(19)(20) to be susceptible to invasion by QS mutants that act as "cheaters" and exploit the public goods produced by a functioning QS strain. Such cheating can be repressed by mechanisms that increase relatedness and lead to preferential assortment of cooperators and cheaters through structured populations (21-24).…”
mentioning
confidence: 99%
“…We share the widespread opinion that the "change of bacterial lifestyle" is crucial for colonizing habitats and infecting susceptible hosts -unfortunately the signalling systems that orchestrate the underlying communication and collaboration mechanisms are not accurately annotated in bacterial genomes. Therefore, a systematic characterization of QS systems in Gram negative bacteria was carried out [68,69] and a modelling effort to map out the theoretically possible consequences of communication and collaboration in bacterial populations was initiated [70][71][72]. Virulence and adaptability of many Gram-negative bacterial species are associated with an N-acylhomoserine lactone (AHL) gene regulation mechanism called quorum sensing (QS).…”
Section: Bacterial Communication and Cooperation In Health And Diseasementioning
confidence: 99%